2016
DOI: 10.21037/jtd.2016.09.66
|View full text |Cite
|
Sign up to set email alerts
|

Amide-linked local anesthetics induce apoptosis in human non-small cell lung cancer

Abstract: Background: A retrospective analysis of patients undergoing cancer surgery suggested that using local anesthetics could reduce cancer recurrence and improve survival rate. Previous studies have indicated that local anesthetics may induce apoptosis in several kinds of cells in vitro, but the mechanism is unclear. Methods: Cell viability was analyzed by MTS; reactive oxygen species (ROS), mitochondrial membrane potential (MMP, ∆Ψm), cell cycle distribution, and cell apoptosis assay were detected by flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 37 publications
3
41
3
2
Order By: Relevance
“…These results suggest that the mechanisms of action of lidocaine on cell viability are different among distinct cell lines. These results are consistent with findings of breast (16,19,22) and other cancer cell types including A549 and H520 human non-small cell lung cancer cells (20), 8505C and K1 human thyroid cancer cells (17), PC-3 prostatic cancer cells and ES-2 ovarian cancer cells (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggest that the mechanisms of action of lidocaine on cell viability are different among distinct cell lines. These results are consistent with findings of breast (16,19,22) and other cancer cell types including A549 and H520 human non-small cell lung cancer cells (20), 8505C and K1 human thyroid cancer cells (17), PC-3 prostatic cancer cells and ES-2 ovarian cancer cells (19).…”
Section: Discussionsupporting
confidence: 91%
“…Perioperative intravenous lidocaine infusion has been shown to reduce postoperative pain and opioid requirements (14,15). Lidocaine has also been shown to induce apoptosis and suppress tumor growth in human breast tumor cells (16) as well as other in vitro tumor cells (12,(17)(18)(19)(20)(21). Additionally, it has been reported to enhance sensitization of breast cancer cells to chemotherapeutic drugs (22).…”
mentioning
confidence: 99%
“…For instance, they can facilitate the apoptosis of human thyroid cancer cells via regulation of the mitogen-activated protein kinase pathway (Chang et al, 2014). Compelling evidence has indicated that Amide-linked local anesthetics contributes to apoptosis of human nonsmall cell lung cancer (Wang et al, 2016). Lidocaine plays significant roles in inhibiting proliferation and promoting apoptosis of F I G U R E 6 ITGA2 overexpression alleviated the effect of Ropivacaine on apoptosis of TPC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vitro and in vivo studies showed that LAs might also have direct effects on certain tumour cells (e.g. breast, lung, liver and thyroid) (15)(16)(17)(18). It has been reported that lidocaine inhibited the growth of HepG2 cells in a dose-dependent and time-dependent manner, arrested cells in the G 0 /G 1 phase of the cell cycle and induced apoptosis (19).…”
Section: Significantly Inhibited the Proliferation Of Ags And Hg-27 Cmentioning
confidence: 99%